The Position and Protection of Elderly in Retail Banking Market in the Perspective of Sustainable Finance - Kłobukowska, Justyna (Journal of Finance and Financial Law, 2016)
In the article the Author tends to present elderly as a new and separate customer segment on the retail banking in the nearest feature. This general assumption leads to define the main goal of the article as an analyse and identification main problems concerned with seniors protection on the retail banking market. The considerations are connected with the sustainable finances. Concluding, elderly protection will be possible when the market reach greater transparency, the banking agreement will be more readable and the financial education will be more popularize among the elderly segment.